A Modification to Enhance the Survival of the Island FDMA Flap by Adding a Skin Bridge - Salim Al Lahham (16515333) (2021)
Background Distal thumb injuries are common in high construction load regions, and it is a challenging task for the plastic surgeon to find the optimum choice that preserves thumb length and provides a sensory substitute to the lost tissue. Introducing first dorsal metacarpal artery flap has solved the dilemma. One drawback is that the flap is susceptible to distal necrosis, which can happen because of tight tunneling or insufficient venous drainage. We combined Foucher and Holevich characteristics to design a flap that promises to solve the problem. Methods This is a case series that includes 9 patients where we describe a technique that has the potential to enhance the survival of the first dorsal metacarpal artery (FDMA) flap and decreases the rate of distal necrosis via addition of a 5-mm skin bridge to the pedicle and by avoiding tunneling. Distal necrosis of the patients in this study patients was compared with that in a control of 10 patients in whom we did the conventional FDMA flap. Patients were followed for 6 weeks to trace early postoperative complications (infection, dehiscence, and necrosis) and the establishment of protective sensation (pain and temperature). Results None of our patients had distal necrosis, infection, or dehiscence, and all had protective sensation in the flap. In comparison, 4 patients in the control group developed distal necrosis. Conclusion FDMA is one of the best choices when it comes to distal thumb reconstruction, but it has the disadvantage of distal necrosis, which might be avoided when using the technique mentioned in this study. Other Information Published in: Plastic and Reconstructive Surgery - Global Open License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1097/gox.0000000000003434